Security aspects of uni-and multimodal hazmat transportation systems - Reniers, Genserik L. L.; Zamparini, Luca (WilVCH, 2012)
Written in a clear language, for use by scholars, managers and decisionmakers, this practical guide to the hot topic is unique in treating thesecurity aspects of hazmat transportation from both uni-modal and multi-modal perspectives. To begin with, each transport mode and itsrelation to security vulnerability, analyses, figures, and approaches is discussed separately. Secondly, the optimization process of a hazmatsupply chain is examined from a holistic, integrated viewpoint. Finally, the book discusses and compares the various hazmat transport securitypolicies and strategies a.